2020
DOI: 10.1080/16078454.2020.1815129
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag, oral immunosuppressant and androgen combination therapy in twelve patients with refractory severe aplastic anemia

Abstract: Objective: Eltrombopag monotherapy or eltrombopag combined with immunosuppressant has achieved robust hematologic responses in severe aplastic anemia (SAA). In patients with refractory SAA, for whom hematopoietic stem cell transplantation is unavailable, we attempted to combine eltrombopag with oral immunosuppressant and androgen, to further improve hematologic response. Methods: We collected and analyzed data retrospectively from twelve refractory SAA cases who had received combination therapy of eltrombopag,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…In a study by Gao et al, they observed that, in total of 12 patients, overall response rate was 42%. 10 In the present study, it was also observed that 73% patients were lost to follow-up (Figure 1). High incidence of AA in India is linked to lower socioeconomic status.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In a study by Gao et al, they observed that, in total of 12 patients, overall response rate was 42%. 10 In the present study, it was also observed that 73% patients were lost to follow-up (Figure 1). High incidence of AA in India is linked to lower socioeconomic status.…”
Section: Discussionsupporting
confidence: 67%
“…9 Eltrombopag is added to this combination if the patient affords this treatment. 10 However, there are limited data published in the literature from India, which highlights the utility of cyclosporine and anabolic steroids. Hence, this study was conducted to know the effect of these medications in patients with AA.…”
Section: Aims and Objectivesmentioning
confidence: 99%
“…Despite having been shown to increase C1-INH mRNA expression, upregulate C1-INH protein levels and promote accelerated degradation of bradykinin to alleviate the symptoms of angioedema, the exact mechanism of androgens requires further study [ 13 , 14 ]. In the last decade, androgens are considered to be effective and commonly used for HAE and other diseases, such as aplastic anemia, testicular insufficiency, and anorchidism [ 15 17 ].…”
Section: Androgen Treatment In Haementioning
confidence: 99%
“…Aged patients usually exhibit poor response to treatment when compared with the younger ones, for either IST or HSCT (35)(36)(37). Under this circumstance, we found that EPAG+IST had a very similar ORR (lower in absolute number) than the haplo-HSCT (81% in the EPAG+IST group and 86% in the haplo-HSCT group, p = 0.23).…”
Section: Discussionmentioning
confidence: 62%
“…However, there was a non-significant higher OS and less death rate, probably due to the small number of patients. These findings imply that EPAG+IST has comparable efficacy and OS with haplo-HSCT, even for younger patients, who are the right candidates for haplo-HSCT (35). So far, there was no head-to-head comparison for the frontline treatment of either EPAG+IST with MSD or EPAG+IST with haplo-HSCT.…”
Section: Discussionmentioning
confidence: 94%